Sampling-based online motion planning for mobile robots: utilization of Tabu search and adaptive neuro-fuzzy inference system - Khaksar W.; Hong T.S.; Sahari K.S.M.; Khaksar M.; Torresen J. (Springer London, 2023)
Adaptive control systems; Controllers; Fuzzy neural networks; Fuzzy systems; Motion planning; Robot programming; Robots; Tabu search; Adaptive neuro fuzzy inference systems (ANFIS); Adaptive neuro-fuzzy inference system; ANFIS; Fuzzy controllers; Motion planning algorithms; Sampling-based algorithms; Sampling-based motion planning; Unknown environments; Fuzzy inference